An earnest perswasive to personal reformation: proposing the true method of making all men happy in this world, and in the world to come. Published for the furtherance and advancement of the reformation recommended by his Majesty; and carried on by the societies in London, and elsewhere. [electronic resource] : (1700)
Summary goes here